2010
DOI: 10.1152/physiolgenomics.00049.2010
|View full text |Cite
|
Sign up to set email alerts
|

Expression and distribution of voltage-gated ion channels in ferret sinoatrial node

Abstract: Brahmajothi MV, Morales MJ, Campbell DL, Steenbergen C, Strauss HC. Expression and distribution of voltage-gated ion channels in ferret sinoatrial node. Physiol Genomics 42A: 131-140, 2010. First published August 3, 2010 doi:10.1152/physiolgenomics.00049.2010.-Spontaneous diastolic depolarization in the sinoatrial (SA) node enables it to serve as pacemaker of the heart. The variable cell morphology within the SA node predicts that ion channel expression would be heterogeneous and different from that in the at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 86 publications
(111 reference statements)
1
6
0
Order By: Relevance
“…The results presented in this study corroborate our previous findings in that the higher-affinity targets of κM-RIIIJ are composed of subunits not abundantly found in cardiomyocytes [for overview, see Nerbonne and Kass (12)]. Curiously, K v 1.1, K v 1.2, and K v 1.6 have been immunodetected in sinoatrial node cells in ferret hearts (13).…”
Section: Discussionsupporting
confidence: 90%
“…The results presented in this study corroborate our previous findings in that the higher-affinity targets of κM-RIIIJ are composed of subunits not abundantly found in cardiomyocytes [for overview, see Nerbonne and Kass (12)]. Curiously, K v 1.1, K v 1.2, and K v 1.6 have been immunodetected in sinoatrial node cells in ferret hearts (13).…”
Section: Discussionsupporting
confidence: 90%
“…To study the myocardial effect of increased I f under conditions that minimized its influence on heart rate, we have generated transgenic mice that express human HCN4 (HCN4 tg/wt ) under control of the murine cTNI promoter. While abundantly expressed in the working myocardium, cTNI is downregulated in the SAN and the conduction system 22 . This is phenotypically reflected by telemetric recordings revealing similar heart rates and conduction parameters in transgenic and wild type mice (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…2E, F). 30 µM TTX was included in our pre-block cocktails because ivabradine has previously been shown to block Na + currents (26) and 30 µM TTX inhibits both weakly TTX-sensitive Nav1.5 channels as well as highly TTX-sensitive Nav1.1 channels expressed in the murine sinoatrial node (42, 43). We found that the Na + -Ca 2+ -K + (NCK) channel blocker cocktail blocked ∼10% of the inward current that was activated during 1 s hyperpolarizations to -120 mV (Fig.…”
Section: Resultsmentioning
confidence: 99%